2019
DOI: 10.18203/2320-1770.ijrcog20191528
|View full text |Cite
|
Sign up to set email alerts
|

Study of management of postpartum hemorrhage and its complications

Abstract: Background: Postpartum hemorrhage (PPH) is globally one of the most common causes of maternal death, especially in developing country like India. Pregnancy and childbirth involve significant health risks, even to women with no preexisting health problem. The objective of this study was to analyze the role of various interventions in the management of PPH and its complications.Methods: This prospective observational study was conducted in the department of obstetrics and gynecology of Department of Obstetrics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 9 publications
0
9
1
2
Order By: Relevance
“…Thawal et al in an observational retrospective study had similar results in which anemia was high risk factor in 70% patients of PPH. 9 Our study shows 89% cases of primary PPH were in 37-40 weeks period of gestation whereas 11% fall between 41-42 weeks period of gestation. The reason for the same could be biologic or pathologic connections like reduced myometrial contractility (including reduced contractile response to exogenous oxytocin), altered placentation and other etiologies with risk of hemorrhage.…”
Section: Resultsmentioning
confidence: 48%
“…Thawal et al in an observational retrospective study had similar results in which anemia was high risk factor in 70% patients of PPH. 9 Our study shows 89% cases of primary PPH were in 37-40 weeks period of gestation whereas 11% fall between 41-42 weeks period of gestation. The reason for the same could be biologic or pathologic connections like reduced myometrial contractility (including reduced contractile response to exogenous oxytocin), altered placentation and other etiologies with risk of hemorrhage.…”
Section: Resultsmentioning
confidence: 48%
“…In this study, the most common causes of postpartum hemorrhage were uterine atony 56.5% and adherent Placenta accreta 43.42%. However, Thawal V et al 3 reported that out of all 77.5% cases had uterine atony, 15.0% patients had perineal trauma, 5.0 seen with retained placenta and 2.5% were females had a bleeding disorder. Also, adherent placental accreta was second most common cause of PPH seen in our study.…”
Section: Resultsmentioning
confidence: 97%
“…mean age of the cases was 29.21±6.208 years with predominantly occurring in multiparous women. Similarly in the study of Thawal V et al3 reported that the average age of the females was 26.4±7.4 years and multiparous women were in majority 60%. In another study by Kebede BA et al10 demonstrated that around 83.9% of females were aged[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] …”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Almutari V, en una revisión de 71 artículos identificó la HPP como causa de mortalidad en el 27% a nivel mundial, así como una prevalencia de HPP a nivel mundial del 10%, África el 25.7%, América Latina y Asia el 8%, América del Norte 21% y en Estados Unidos fue superior el 27%. Incidiendo en Estados Unidos la HPP en la mortalidad en el 46.6% de los casos estando entre las causas principales anemia, shock hipovolémico, coagulación intravascular diseminada, déficit respiratorio agudo, insuficiencia renal y en el 70-80% la casusa más común la atonía uterina (Thawal et al, 2019).…”
Section: Documentos Completos Evaluados N=68unclassified